Surveillance in hospitalized children with infectious diseases in Japan: Pre- and post-coronavirus disease 2019. Issue 11 (November 2021) - Fukuda, Yuya; Tsugawa, Takeshi; Nagaoka, Yoshinobu; Ishii, Akira; Nawa, Tomohiro; Togashi, Atsuo; Kunizaki, Jun; Hirakawa, Satoshi; Iida, Junya; Tanaka, Toju; Kizawa, Toshitaka; Yamamoto, Dai; et al.
Abstract: Introduction: The epidemic of coronavirus disease 2019 (COVID-19) rapidly spread worldwide, and the various infection control measures have a significant influence on the spread of many infectious diseases. However, there have been no multicenter studies on how the number of hospitalized children with various infectious diseases changed before and after the outbreak of COVID-19 in Japan. Methods: We conducted a multicenter, prospective survey for hospitalized pediatric patients in 18 hospitals in Hokkaido Prefecture, Japan, from July 2019 to February 2021. We defined July 2019 to February 2020 as pre-COVID-19, and July 2020 to February 2021 as post-COVID-19. We surveyed various infectious diseases by sex and age. Results: In total, 5300 patients were hospitalized during the study period. The number of patients decreased from 4266 in the pre-COVID-19 period to 701 (16.4%) post-COVID-19. Patients with influenza and RSV decreased from 308 to 795 pre-COVID-19 to zero and three (0.4%) post-COVID-19. However, patients with adenovirus (respiratory infection) only decreased to 60.9% (46–28) of pre-COVID levels. Patients with rotavirus, norovirus, and adenovirus gastroenteritis decreased markedly post-COVID-19 to 2.6% (38–1), 27.8% (97–27) and 13.5% (37–5). The number of patients with UTIs was similar across the two periods (109 and 90). KD patients decreased to 31.7% (161–51) post-COVID-19. Conclusions: We suggest that current infection control measures for COVID-19 such as wearing masks, washing hands, and disinfecting hands with alcohol are effective against various infectious diseases. However, these effects vary by disease.